A novel natural environment background model for Monte Carlo simulation and its application in the simulation of anticoincidence measurement. (February 2016) - Li, Sangang; Wang, Lei; Cheng, Yi; Tuo, Xianguo; Liu, Mingzhe; Yao, Fuliang; Leng, Fengqing; Cheng, Yuanyuan; Cai, Ting; Zhou, Yan
Abstract: This study proposes a novel natural environment background model by modeling brief environment conditions. It uses Geant4 program to simulate decays of 238 U, 232 Th, and 40 K in soil and obtains compositions of different-energy gamma rays in the natural environment background. The simulated gamma spectrum of the natural environment background agrees well with the experimental spectrum, particularly above 250 keV. The model is used in the simulation of anticoincidence measurement, indicating that the natural environment background can be decreased by approximately 88%, and the Compton attenuation factor is 2.22. The simulation of anticoincidence measurement can improve the minimum detectable activity (MDA) of the detection system. Highlights: This study proposes a novel natural environment background model by simulating decays of 238 U, 232 Th, and 40 K in soil. The simulated gamma spectrum of the natural environment background agrees well with the experimental spectrum, particularly above 250 keV. The proposed environment background model is applied to study the properties of anticoincidence detector.